Changes in The Mental Health Condition Among Elderly After Giving Reflexology Massage Intervention - Putri, Dewi Atika; Kang, Hari Iskandar; Winda, Anindini; Subu, Muhammad Arsyad; Handayani, Dwi Ratna Sari; Rosita, Hafna (Syntax Corporation Indonesia, 2023)
Introduction: The number of elderly people in Indonesia is estimated to rise by about 10 percent and by 2024 it will rise to 20 percent and this group is facing issues such as living below the poverty line, health problems such as mental health (depression and anxiety) Various instruments of mental health are widely used both in hospitals and in the community Objective: The objective of this study was to know the changes in the mental health condition of elders after given reflexology intervention Methods: This is quasi experimental study with pre and post design among elder group ≥ 60 years. The elderly people were interviewed with GDS and GAT-7 before receiving treatment. The following step consisted of alternate massaging the legs using reflexology. After completing the reflexology massage intervention every 2 (two) times a week with a duration of 100-140 minutes, the second GDS and GAT-7 interview was then conducted. The results of the difference in the average scores of GDS and GAT-7 were compared to see the extent of the benefits of reflexology intervention in reducing anxiety and depression in the elderly group. Other variables are age, marriage status, education, research carried out in Puraseda village, Leuwiliang district, Bogor district of West Java. Sampling method uses random sampling techniques that meet the inclusion criteria with a minimum sample size of 10. Analysis is performed in a descriptive and bivariate to see the difference between GS and GAT-7 scores. Results: The overall average GDS score decreased after being given reflexology massage. Our study found that there was an influence of reflexology on the elderly mental health. The average depression score before reflexology was 18.60 with a standard deviation of 3.01. Then, an average depression score after reflexology intervention was 16.20 with a standard deviation of 2.68. In this study, the anxiety score was carried out using the Wilcoxon test, where 7 subjects’ anxiety levels decreased, 3 subjects’ anxiety levels increased, and 5 subjects remained the same.